Paraquat Degradation From Contaminated Environments: Current Achievements and Perspectives - Huang, Yaohua; Zhan, Hui; Bhatt, Pankaj; Chen, Shaohua (Frontiers in Microbiology, 2019)
Paraquat herbicide has served over five decades to control annual and perennial weeds in agriculture, forestry and urban greening. Despite of agricultural benefits, its pollution to terrestrial and aquatic environments raises serious concerns. Paraquat is not rapidly degraded in the environment and is rather adsorbed in clay lattices that requires urgent environmental remediation. Advanced oxidation processes and bioaugmentation techniques have been developed for this purpose. Among various techniques, bioremediation is considered as a cost-effective and eco-friendly approach for pesticide polluted soils. Though several paraquat-degrading microorganisms have been isolated and characterized, research still lacks the studies on its degradation pathways, related functional enzymes and genes. This review encircles the paraquat removal from contaminated environments through adsorption, photocatalyst degradation, advanced oxidation processes and microbial degradation. To provide the in-depth knowledge, article also comprehensively discusses the potential role of paraquat degrading microorganisms in bioremediation of contaminated environments.